Modified organic perovskite nanocrystal and preparation method thereof
By using silazane coupling agent to modify and coat the organic perovskite nanocrystals during the hydrolysis and coating process, the problem of poor stability of nanocrystals in the traditional hydrolysis and coating process is solved, and modified nanocrystals with high stability and high luminous properties are achieved.
Patent Information
- Application Number
- CN202311235681.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-22
- Publication Date
- 2025-03-25
AI Technical Summary
In the prior art, during the hydrolysis and coating process, organic perovskite nanocrystals are difficult to maintain stability, resulting in a decrease in luminescence performance or quenching.
The organic perovskite nanocrystals are modified by using a silazane coupling agent to form ammonia by hydrolysis of the silazane coupling agent to prevent the decomposition of the organic perovskite nanocrystals and uniformly coated with silica on its surface.
The stability and luminescence performance of organic perovskite nanocrystals are significantly improved, and the failure and performance of nanocrystals are avoided during hydrolysis and coating.
Smart Images

Figure CN119685001A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of perovskite, and specifically relates to a modified organic perovskite nanocrystal and a preparation method thereof. Background Art
[0002] In recent years, halogen perovskite APbX3 (A=MA + , F.A. + or Cs + ; X=Cl - ,Br - or I - ) nanocrystals have attracted wide attention due to their excellent optoelectronic properties and have great application potential. Among them, the luminescence wavelength of formamidine / methylamine bromide (FAPbBr3 / MAPbBr3) organic perovskite nanocrystals is in the range of 520-540nm. As a display luminescent material, it has unique advantages, with purer green, no need for halogen doping, and no phase separation problem.
[0003] However, compared with pure inorganic perovskite nanocrystals of CsPbBr3, the structure of organic perovskite nanocrystals is more fragile and more susceptible to the external environment. Nanocrystals are easily decomposed and have poor stability. For practical applications, they need to be coated with a dense shell to resist water and oxygen. The current coating technology usually uses silane coupling agents such as TEOS and APTES to hydrolyze and coat the nanocrystals. This method is low-cost, simple to operate, and very suitable for commercial mass production.
[0004] However, this traditional hydrolysis coating process will produce alcohols such as ethanol and methanol, as well as trace amounts of water. It is difficult for organic perovskite nanocrystals to remain stable in such an environment, and their luminescence performance will usually decrease or even quench. Summary of the invention
[0005] Therefore, the technical problem to be solved by the present invention is to overcome the defect in the prior art that organic perovskite nanocrystals are difficult to maintain stability during the hydrolysis coating process, thereby providing a modified organic perovskite nanocrystal and a preparation method thereof.
[0006] To this end, the present invention provides the following technical solutions.
[0007] In one aspect, the present invention provides a method for preparing modified organic perovskite nanocrystals, comprising the following steps:
[0008] Step 1: Prepare an organic perovskite nanocrystal dispersion, wherein the organic perovskite nanocrystal is APbX3, wherein A is MA + or FA + ; X includes Cl - ,Br - and I - At least one of;
[0009] Step 2, adding a silazane coupling agent to the organic perovskite nanocrystal dispersion to react and obtain modified organic perovskite nanocrystals;
[0010] The general formula of the silazane coupling agent is N(Si(OR)3)3, wherein R is an alkyl group.
[0011] Furthermore, the R is ethyl or isopropyl.
[0012] Tris(triethoxysilyl)amine:
[0013] Tris(triisopropoxysilyl)amine:
[0014] Furthermore, in step 2, the amount of silazane coupling agent added is 20 to 200 μL, preferably 80 μL, per 100 mg of organic perovskite nanocrystals.
[0015] Furthermore, in step 2, the reaction temperature is 25-60°C, preferably room temperature 25°C.
[0016] In one possible design, in step 2, after adding the silazane coupling agent to the organic perovskite nanocrystal dispersion, the mixture is stirred in the air for a period of time, and then reacted under sealed conditions. Stirring in the air first absorbs water in the air so that the silazane coupling agent can be hydrolyzed, and then reacting under sealed conditions to prevent the escape of ammonia generated by the hydrolysis.
[0017] Preferably, the stirring time in air is 10 to 60 minutes, for example, stirring for 30 minutes. Preferably, the reaction time under sealed conditions is 10 to 50 hours, preferably 15 hours. Preferably, the reaction temperature under stirring and / or sealed conditions under air is 25 to 60° C., preferably room temperature 25° C.
[0018] Furthermore, the step 1 adopts a solution method to prepare an organic perovskite nanocrystal dispersion;
[0019] Optionally, the solution method is a hot injection method, an anti-solvent method or a room temperature method.
[0020] Furthermore, the step 1 comprises: mixing the perovskite A-site organic cation source, the lead source, the surface ligand and the solvent to prepare a precursor solution, and then adding the halogen source to the precursor solution.
[0021] Furthermore, step 1 satisfies at least one of the following conditions:
[0022] (1) The organic cation source at the A position of the perovskite is acetic acid formamidine or methylamine acetate;
[0023] (2) The lead source is lead acetate trihydrate;
[0024] (3) The surface ligand is at least one of oleic acid, oleylamine, tetradecylphosphonic acid, and dodecylbenzenesulfonic acid;
[0025] (4) one or more of the solvents octadecene, trimethylolbenzene, xylene, toluene, and n-hexane;
[0026] (5) The halogen source is any one of a quaternary ammonium halogenide salt and a halogenated oleylamine salt, or a combination of several thereof; preferably, the quaternary ammonium halogenide salt is selected from any one of dioctadecyl dimethyl ammonium bromide, didodecyl dimethyl ammonium bromide, dioctadecyl dimethyl ammonium iodide, didodecyl dimethyl ammonium iodide, dioctadecyl dimethyl ammonium chloride, and didodecyl dimethyl ammonium chloride; the halogenated oleylamine salt is one of oleylamine bromide, oleylamine iodide, and oleylamine chloride.
[0027] In a second aspect, the present invention provides a modified organic perovskite nanocrystal prepared according to the above method.
[0028] The technical solution of the present invention has the following advantages:
[0029] 1. The method for preparing modified organic perovskite nanocrystals provided by the present invention comprises the following steps: Step 1, preparing an organic perovskite nanocrystal dispersion, wherein the organic perovskite nanocrystal is APbX3, wherein A is MA + or FA + ; X is Cl - ,Br - and I - At least one of the following; step 2, adding a silazane coupling agent to the organic perovskite nanocrystal dispersion to react and obtain modified organic perovskite nanocrystals; the silazane coupling agent has the general formula N(Si(OR)3)3, wherein R is an alkyl group.
[0030] The present invention adopts a silazane coupling agent, and the hydrolysis of the silazane coupling agent is as follows: the silicon-nitrogen bond is first broken to generate NH3 and Si(OR)3OH, and Si(OR)3OH continues to hydrolyze, and the carbon-oxygen bond is broken to generate orthosilicic acid Si(OH)4 and ROH, and the orthosilicic acid is dehydrated and condensed on the surface of the organic perovskite nanocrystal to form a dense protective layer.
[0031] After the methylamine cation and the formamidine cation are deprotonated, the organic small molecule materials such as methylamine and formamidine formed are themselves very unstable and are very easy to decompose after contacting water, alcohol, etc. generated during the hydrolysis of the silane coupling agent, and corrode from the surface to the inside, resulting in the loss of the A site of the organic perovskite nanocrystal, structural collapse, and reduced luminescence performance; the ammonia gas generated by the hydrolysis of the silazane coupling agent added in the present invention can prevent the decomposition of methylamine and formamidine, reversely promote methylamine and formamidine to recover formamidine cations or methylamine cations, and prevent them from being deprotonated again, thereby ensuring that the surface and internal structure of the organic perovskite nanocrystal are not destroyed, thereby playing a role in protecting and repairing the organic perovskite nanocrystal, and uniformly coating a layer of silicon dioxide on the surface of the organic perovskite nanocrystal while maintaining the stability of the organic perovskite nanocrystal.
[0032] Moreover, after the coating is completed, since ammonia is a gas, it will evaporate directly and will not remain in the solution to affect the luminescence properties of the modified organic perovskite nanocrystals.
[0033] 2. In the preparation method of the modified organic perovskite nanocrystals provided by the present invention, the amount of silazane coupling agent added is 20 to 200 μL of silazane coupling agent per 100 mg of organic perovskite nanocrystals, preferably 80 μL. Within this range, the organic perovskite nanocrystals can be ensured not to fail during the coating process and retain high luminescence performance.
[0034] 3. The preparation method of the modified organic perovskite nanocrystal provided by the present invention has a reaction temperature of 25 to 60° C., preferably room temperature 25° C. The present invention does not require high temperature operation during the coating process, and the reaction conditions are mild. It can be applied to all nanocrystal dispersions, and has little damage to the nanocrystals, thereby avoiding the degradation of the performance of the prepared modified organic perovskite nanocrystals. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0036] Figure 1 This is a stability comparison chart of the FAPbBr3 dispersion prepared in step 1 and the product of step 2 in Example 1;
[0037] Figure 2 It is a signal intensity diagram of the modified organic perovskite nanocrystals prepared in Example 1 and Comparative Example 1 under the same excitation light conditions. DETAILED DESCRIPTION
[0038] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the guidance of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.
[0039] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0040] Example 1
[0041] This embodiment provides a method for preparing modified organic perovskite nanocrystals, comprising the following steps:
[0042] Step 1: Prepare organic perovskite nanocrystal dispersion by hot injection method:
[0043] Take 0.54mmol of acetic acid formamidine, 0.27mmol of lead acetate trihydrate, and 1.89mmol of DBSA (dodecylbenzenesulfonic acid) in a 100ml three-necked flask, add 10ml of ODE (octadecene), remove the air by vacuuming at room temperature, and then pass N2. Heat to 60°C and stir until the precursor salt is completely dissolved, then heat to 120°C, open the vacuum for 30min, pass N2, and quickly inject the pre-configured DDOAB solution (0.675mmol DDOAB (dioctadecyl dimethyl ammonium bromide) dissolved in 1ml of trimethylol), react for 5s, and ice water bath to obtain a crude solution. Add 3 times the volume of ethyl acetate to the crude solution, centrifuge at 8000rpm for 5min to obtain a precipitate, add 10ml of n-hexane, centrifuge at 4000rpm for 5min to obtain the supernatant, and obtain an organic perovskite nanocrystal FAPbBr3 dispersion, the organic perovskite nanocrystal content concentration in the dispersion is about 10mg / ml.
[0044] Step 2: Take 5 ml of the FAPbBr3 dispersion prepared in step 1, place it in a 20 mL small glass bottle, add 40 μL of tri(triisopropoxysilyl)amine, stir at room temperature with the lid open for 30 min, then cover the bottle and stir at room temperature for 15 h.
[0045] Step 3, washing and purification: centrifuge the liquid after the reaction in step 2 at 5000 rpm for 5 minutes, take the precipitated powder, discard the supernatant, wash the powder with n-hexane for 3 times, and finally dry the powder in a forced air drying oven to obtain green modified organic perovskite nanocrystals FAPbBr3@SiO2.
[0046] The quantum efficiency of FAPbBr3 prepared in step 1 of this embodiment is 96%, the luminescence peak is 532nm, and the half-peak width is 20nm.
[0047] The FAPbBr3@SiO2 prepared in step 3 has a quantum efficiency of 95%, a luminescence peak of 533.5 nm, and a half-peak width of 21 nm, with no significant difference in performance compared to before coating.
[0048] Example 2
[0049] This embodiment provides a method for preparing modified organic perovskite nanocrystals, which is basically the same as that of Embodiment 1, except that the formamidine acetate in step 1 of Embodiment 1 is replaced by an equal molar amount of methylamine acetate.
[0050] The quantum efficiency of MAPbBr3 prepared in step 1 of this embodiment is 90%, the luminescence peak is 525nm, and the half-peak width is 23nm.
[0051] The quantum efficiency of MAPbBr3@SiO2 prepared in step 3 is 89%, the luminescence peak is 527nm, and the half-peak width is 24nm, which has no significant difference from the performance before coating.
[0052] Example 3
[0053] This embodiment provides a method for preparing modified organic perovskite nanocrystals, comprising the following steps:
[0054] Step 1: Prepare organic perovskite nanocrystal dispersion by room temperature method:
[0055] 26mg of acetic acid formamidine (0.25mmol), 95mg of lead acetate trihydrate (0.25mmol) were placed in a 20ml glass vial, 0.75ml of oleic acid (OA) toluene solution (concentration of 1mmol / ml) was added, and then an appropriate amount of toluene was added to adjust the volume of the precursor solution to 5ml. The precursor solution was placed on a magnetic stirring table and heated and stirred at 60°C until the mixed solution changed from turbid to clear, indicating that the reaction was completed. At room temperature, the prepared 0.75ml toluene solution of oleylamine bromide (OAmBr) (10mmol dissolved in 10ml toluene, concentration 1mmol / ml) was quickly injected into the precursor solution and stirred rapidly (800rpm), and the solution quickly changed from colorless and clear to yellow-green, and the stirring reaction time was 5 minutes. The reacted solution was directly centrifuged at a speed of 7000rpm for 3 minutes. After the centrifugation, the upper layer liquid obtained was the organic perovskite nanocrystal FAPbBr3 dispersion, and the concentration of organic perovskite nanocrystals in the dispersion was about 15mg / ml.
[0056] Step 2: Take 5 ml of the FAPbBr3 dispersion prepared in step 1, place it in a 20 mL small glass bottle, add 30 μL of tri(triisopropoxysilyl)amine, stir with the lid open for 30 min, then cover and stir for 15 h.
[0057] Step 3, washing and purification: centrifuge the liquid after the reaction in step 2 at 5000 rpm for 5 minutes, take the precipitated powder, discard the supernatant, wash the powder with n-hexane for 3 times, and finally dry the powder in a forced air drying oven to obtain green organic perovskite nanocrystals FAPbBr3@SiO2.
[0058] The quantum efficiency of FAPbBr3 prepared in step 1 of this embodiment is 95%, the luminescence peak is 530nm, and the half-peak width is 22nm.
[0059] The quantum efficiency of FAPbBr3@SiO2 prepared in step 3 is 94%, the luminescence peak is 531nm, and the half-peak width is 23nm. After being coated with the silica shell, the modified organic perovskite nanocrystal prepared in this embodiment can still maintain a high quantum efficiency.
[0060] Example 4
[0061] This embodiment provides a method for preparing modified organic perovskite nanocrystals, which is basically the same as that of Embodiment 1, except that in step 2, the mixture is covered with a lid and stirred at room temperature for 50 hours.
[0062] Because the silica coating time was too long and the coating was too thick, agglomeration occurred and the coating effect was slightly reduced. The quantum efficiency of the obtained FAPbBr3@SiO2 was 85%, the luminescence peak was 534nm, and the half-peak width was 22.5nm.
[0063] Example 5
[0064] This embodiment provides a method for preparing modified organic perovskite nanocrystals, which is basically the same as that of Embodiment 1, except that, in step 2, stirring is performed at 50° C. for 30 min with the lid open, and then stirring is performed at 50° C. for 15 h with the lid closed.
[0065] As the temperature increases, the hydrolysis rates of the first and second steps are accelerated. At this time, the coating time of Example 1 is maintained, and the nanocrystals are easily agglomerated during the coating process, and the coating uniformity decreases. The quantum efficiency of the obtained FAPbBr3@SiO2 is 88%, the luminescence peak is 533nm, and the half-peak width is 24nm.
[0066] Example 6
[0067] This embodiment provides a method for preparing modified organic perovskite nanocrystals, which is basically the same as that of Embodiment 1, except that in step 2, the amount of tri(triisopropoxysilyl)amine added is 10 μL.
[0068] Compared with Example 1, the amount of silazane coupling agent added in this example is lower, and the NH3 and coating material produced by hydrolysis are less, resulting in a slight decrease in the protection and coating effect of the organic perovskite nanocrystals. The obtained FAPbBr3@SiO2 has a quantum efficiency of 89%, a luminescence peak of 533nm, and a half-peak width of 21.5nm.
[0069] Example 7
[0070] This embodiment provides a method for preparing modified organic perovskite nanocrystals, which is basically the same as that of Embodiment 1, except that in step 2, the amount of tri(triisopropoxysilyl)amine added is 100 μL.
[0071] Compared with Example 1, the amount of silazane coupling agent added in this example is higher, the shell of the organic perovskite nanocrystal is thicker, and it presents a state of large particle powder. The obtained modified organic perovskite nanocrystal is larger in size, and the optical performance is slightly reduced. The quantum efficiency of the obtained FAPbBr3@SiO2 is 88%, the luminescence peak is 533.5nm, and the half-peak width is 22nm.
[0072] Comparative Example 1
[0073] This comparative example provides a method for preparing modified organic perovskite nanocrystals, which is basically the same as Example 1, except that in step 2, tri(triisopropoxysilyl)amine is replaced by tetramethoxysilane (TMOS).
[0074] Since no ammonia is produced, it cannot protect the organic perovskite nanocrystals, the structure of the organic perovskite nanocrystals is destroyed, and the luminescence performance is greatly reduced. The final modified organic perovskite nanocrystals are orange-yellow powder with a quantum efficiency of 32%, a luminescence peak of 537nm, and a half-peak width of 24nm.
[0075] Test example
[0076] 1. The stability of the organic perovskite nanocrystals before and after coating in Example 1 was tested. The test method was as follows: first, 2 ml of the uncoated nanocrystal n-hexane dispersion solution was taken, and after the solvent was drained, glue (0.3 g isobornyl acrylate (IBOA, Aladdin reagent), 0.7 g polyurethane acrylate 9014 (Sartomer), 0.01 g 1173 photoinitiator (Foshan Qingbai Chemical)) was mixed, coated at a speed of 20 mm / s, and then light-cured at 365 nm for 60 s to obtain a quantum dot optical film. Other coating and film-making methods were consistent with this; the incident light of the fluorescence spectrometer was adjusted to 420 nm, and the intensity was 20000 CPS unchanged. The initial brightness of the optical film before coating was tested to be 4651 count intensity, which was recorded as the initial result; similarly, an appropriate amount of coated quantum dot powder (i.e., the modified organic perovskite nanocrystal obtained in Example 1) 30 mg was taken and mixed with glue to prepare a quantum dot optical film, so that the initial brightness was close to that of the quantum dot optical film of the uncoated sample, and the intensity was adjusted to 4510 counts. For comparison, two quantum dot optical films were placed in water at the same time, taken out at regular intervals, and the incident light of the fluorescence spectrometer was adjusted to 420 nm, and the intensity was 20000 CPS unchanged. The intensity of the luminescent signal was monitored and recorded as aging data.
[0077] The test results are as follows Figure 1 As shown, the luminescence signal intensity of the quantum dots after coating did not show obvious attenuation for 200 minutes, which shows that the stability of the modified organic perovskite nanocrystals is significantly improved.
[0078] 2. The signal intensity of the modified organic perovskite nanocrystals prepared in Example 1 and Comparative Example 1 under the same excitation light conditions was tested. The testing method was as follows: first, 30 mg of the modified organic perovskite nanocrystals of Example 1 and Comparative Example 1 were respectively mixed with the same mass of glue to prepare a quantum dot optical film, and the incident light of the fluorescence spectrometer was adjusted to 420 nm and the intensity was kept constant at 20,000 CPS. The luminescence signal intensity of the quantum dot solution was tested respectively and recorded as the experimental results.
[0079] The test results are as follows Figure 2 As shown by Figure 2 It can be seen that the luminescence signal intensity of the modified organic perovskite nanocrystals of the present invention is significantly improved. In the hydrolysis and coating process of Comparative Example 1, the organic perovskite nanocrystals are difficult to maintain stability, resulting in a decrease in the quantum efficiency of the modified organic perovskite nanocrystals obtained, and some organic perovskite nanocrystals fail, causing a significant decrease in signal intensity. The generation of NH3 during the hydrolysis process of the present invention can maintain the stability of the organic perovskite nanocrystals and avoid the failure of the organic perovskite nanocrystals and the decrease in quantum efficiency.
[0080] Obviously, the above embodiments are merely examples for clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.
Claims
1. A method for preparing modified organic perovskite nanocrystals, characterized in that: The following steps are involved: Step 1: Prepare an organic perovskite nanocrystal dispersion, wherein the organic perovskite nanocrystal is APbX3, wherein A is MA + or FA + ; X includes Cl - ,Br - and I - At least one of; Step 2, adding a silazane coupling agent to the organic perovskite nanocrystal dispersion to react and obtain modified organic perovskite nanocrystals; The general formula of the silazane coupling agent is N(Si(OR)3)3, wherein R is an alkyl group.
2. The method for preparing modified organic perovskite nanocrystals according to claim 1, characterized in that: The R is ethyl or isopropyl.
3. The method for preparing modified organic perovskite nanocrystals according to claim 1 or 2, characterized in that: In the step 2, the amount of silazane coupling agent added is 20 to 200 μL of silazane coupling agent per 100 mg of organic perovskite nanocrystals.
4. The method for preparing modified organic perovskite nanocrystals according to claim 1 or 2, characterized in that: In the step 2, the reaction temperature is 25-60°C.
5. The method for preparing modified organic perovskite nanocrystals according to claim 1 or 2, characterized in that: In the step 2, the reaction time is 10 to 50 hours.
6. The method for preparing modified organic perovskite nanocrystals according to claim 1 or 2, characterized in that: The step 1 adopts a solution method to prepare an organic perovskite nanocrystal dispersion.
7. The method for preparing modified organic perovskite nanocrystals according to claim 6, characterized in that: The solution method is a hot injection method, an anti-solvent method or a room temperature method.
8. The method for preparing modified organic perovskite nanocrystals according to claim 1 or 2, characterized in that: The step 1 comprises: mixing a perovskite A-site organic cation source, a lead source, a surface ligand and a solvent to prepare a precursor solution, and then adding a halogen source to the precursor solution.
9. The method for preparing modified organic perovskite nanocrystals according to claim 8, characterized in that: The step 1 satisfies at least one of the following conditions: (1) The organic cation source at the A position of the perovskite is acetic acid formamidine or methylamine acetate; (2) The lead source is lead acetate trihydrate; (3) The surface ligand is at least one of oleic acid, oleylamine, tetradecylphosphonic acid, and dodecylbenzenesulfonic acid; (4) one or more of the solvents octadecene, trimethylolbenzene, xylene, toluene, and n-hexane; (5) The halogen source is any one of a quaternary ammonium halogenide salt and a halogenated oleylamine salt, or a combination of several thereof; preferably, the quaternary ammonium halogenide salt is selected from any one of dioctadecyl dimethyl ammonium bromide, didodecyl dimethyl ammonium bromide, dioctadecyl dimethyl ammonium iodide, didodecyl dimethyl ammonium iodide, dioctadecyl dimethyl ammonium chloride, and didodecyl dimethyl ammonium chloride; the halogenated oleylamine salt is one of oleylamine bromide, oleylamine iodide, and oleylamine chloride.
10. The modified organic perovskite nanocrystal prepared according to the method according to any one of claims 1 to 9.
Citation Information
Cited By
Perovskite nanocrystalline single particle packaging method based on ammonia water vapor induction and ligand confinement
CN120555060A